Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/rs11192257
|View full text |Cite
|
Sign up to set email alerts
|

A New Algorithm to Estimate Chlorophyll-A Concentrations in Turbid Yellow Sea Water Using a Multispectral Sensor in a Low-Altitude Remote Sensing System

Abstract: In this study, a low-altitude remote sensing (LARS) observation system was employed to observe a rapidly changing coastal environment-owed to the regular opening of the sluice gate of the Saemangeum seawall-off the west coast of South Korea. The LARS system uses an unmanned aerial vehicle (UAV), a multispectral camera, a global navigation satellite system (GNSS), and an inertial measurement unit (IMU) module to acquire geometry information. The UAV system can observe the coastal sea surface in two dimensions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Mobley (1999) provides the recommendation of collecting radiance measurements at viewing directions of θ 40°from nadir and ɸ 135°from the sun to minimize the effects of sun glint and nonuniform sky radiance with a ⍴ value of 0.028. The suggested viewing geometries and ⍴ value from Mobley (1999) have been used to estimate and remove L SR in UAS remote sensing studies (Ruddick et al, 2006;Shang S. et al, 2017;Baek et al, 2019;Kim et al, 2020). However, more recent studies have shown that ⍴ can be spectrally dependent due to the degree of sky polarization and the ratio of diffuse to direct light; assuming a spectally constant ⍴ in a roughened sea surface with multi-angular wave facets can lead to erroneous estimates of L SR (Lee et al, 2010;Mobley, 2015).…”
Section: Background/theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Mobley (1999) provides the recommendation of collecting radiance measurements at viewing directions of θ 40°from nadir and ɸ 135°from the sun to minimize the effects of sun glint and nonuniform sky radiance with a ⍴ value of 0.028. The suggested viewing geometries and ⍴ value from Mobley (1999) have been used to estimate and remove L SR in UAS remote sensing studies (Ruddick et al, 2006;Shang S. et al, 2017;Baek et al, 2019;Kim et al, 2020). However, more recent studies have shown that ⍴ can be spectrally dependent due to the degree of sky polarization and the ratio of diffuse to direct light; assuming a spectally constant ⍴ in a roughened sea surface with multi-angular wave facets can lead to erroneous estimates of L SR (Lee et al, 2010;Mobley, 2015).…”
Section: Background/theorymentioning
confidence: 99%
“…UAS fill an operational gap between in situ and satellite remote sensing methods. While the current available commercial multispectral UAS sensor technology is geared toward terrestrial applications, mostly precision agriculture, the spectral bands have been useful in retrieving water quality parameters in aquatic water bodies (Choo et al, 2018;Arango and Nairn, 2019;Baek et al, 2019;Castro et al, 2020;Olivetti et al, 2020). A UAS sensor package designed for aquatic environments would undoubtedly improve remotely sensed retrievals and water quality measurements.…”
Section: Management Implications and Future Researchmentioning
confidence: 99%
“…However, the recent surge in coastal activities such as aquaculture, tourism, and in blue economy sectors, has led to the disturbance of the ecological structure of the coastal marine environment as well as to a progressive nutrient enrichment of coastal waters. In turn, this is promoting phenomena such as eutrophication, hypoxia, or the death of aquatic animal and plant species [2][3][4]. This is due to the fact that the increase in levels of dissolved phosphorus and nitrogen in coastal waters can lead to excessive growth of algae, phytoplankton, and vegetation close to the water surface [5].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods for water-quality monitoring required the collection of in situ water samples and a subsequent laboratory analysis for the extraction of the optical properties of water [1,3,4,10]. However, despite their high degree of analytical accuracy, these techniques are time-consuming, labor-intensive, and expensive [4,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation